2016
DOI: 10.1002/jbm.a.35675
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, distribution, and impact of distinctly segmented microparticles on cochlear health following in vivo infusion

Abstract: Delivery of pharmaceuticals to the cochleae of patients with auditory dysfunction could potentially have many benefits from enhancing auditory nerve survival to protecting remaining sensory cells and their neuronal connections. Treatment would require platforms to enable drug delivery directly to the cochlea and increase the potential efficacy of intervention. Cochlear implant recipients are a specific patient subset that could benefit from local drug delivery as more candidates have residual hearing; and sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Expanding on their previous work, Ross et al then proceeded to use their Janus particles for the delivery of drugs to the cochleae in an animal model of cochlear implants. By using piribedil loaded microparticles, they were able to show extended release in vivo . These controlled release studies illustrate that the range of degradation and processability afforded with Ac-DEX is much greater than that which is observed with PLGA, leading to better controlled release systems, as included in reviews by Miladi et al and Chifiriuc et al…”
Section: Controlled Releasementioning
confidence: 73%
“…Expanding on their previous work, Ross et al then proceeded to use their Janus particles for the delivery of drugs to the cochleae in an animal model of cochlear implants. By using piribedil loaded microparticles, they were able to show extended release in vivo . These controlled release studies illustrate that the range of degradation and processability afforded with Ac-DEX is much greater than that which is observed with PLGA, leading to better controlled release systems, as included in reviews by Miladi et al and Chifiriuc et al…”
Section: Controlled Releasementioning
confidence: 73%
“…[22][23][24][25][26] Additionally, within these systems, the incorporation of water-based and organicbased polymers, 25,[27][28][29] functional polymers for the creation of specific targeting and stealth patches on the surface of the particles, 30,31 stimuliresponsive polymers for on-demand therapeutic release kinetics, [32][33][34] small molecule-based therapeutics, [33][34][35] DNA-based therapeutics, 36 protein-based therapeutics, 35 and imaging agents 22 have been explored. Furthermore, the interaction of such systems with various cell types, 34,[36][37][38][39][40][41] their biodistribution in vivo, 42 and their functionality as carriers for dual therapeutic delivery to the cochlea 35,43 have demonstrated that multifunctional systems fabricated based on EHD co-jetting can be ideal carriers for targeted delivery in various applications. To date, the majority of these studies have been accomplished using microparticles, and while some have contained nanoparticles, 36,37,42 a systematic study into the fabrication of uniform, multifunctional nanoparticles using the EHD co-jetting system has not been reported.…”
mentioning
confidence: 99%
“…Electrohydrodynamic (EHD) co‐jetting has been used to prepare more complex particles including multicompartmental micro‐ and nanoparticles with various applications in drug delivery. [ 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ] EHD co‐jetting utilizes two or more needles as capillaries in a side‐by‐side configuration. The input solutions are pumped into the needles at a flow rate forming laminar flow to ensure a stable interface between the jetting solutions.…”
Section: Liquid Atomization Methodsmentioning
confidence: 99%